Maqashid Syariah-Based Optimization of Cash Waqf: A Governance Analysis of Structural Constraints and Productive Economic Empowerment Strategies in Indonesia - Fauzan Ghafur; Bahir Mukhammad; Yessi Kurnia Arjani Manik; Gatot Teguh Arifyanto; Dita Kartika Sari Hasibuan; Syahrial Arif Hutagalung (Jurnal IPTEK Bagi Masyarakat, 2026)
Cash waqf (wakaf uang) represents a significant Islamic philanthropic instrument with considerable potential for productive economic empowerment and poverty alleviation. Despite an estimated national potential exceeding IDR 180 trillion annually, actual realization remains below 1% due to complex structural barriers. This study aims to analyze the strategic role of cash waqf in productive economic empowerment while identifying key constraints and optimization strategies within a maqashid syariah framework. Employing a qualitative descriptive-analytical systematic literature review, the research reviewed legislation, fatwas, institutional reports, and peer-reviewed articles published between 2015–2025. Findings reveal three principal results: (1) cash waqf possesses a robust legal foundation through Law No. 41 of 2004 and MUI Fatwa No. 2 of 2002, yet a significant implementation gap persists between legal norms and field practice; (2) primary constraints are systemic and interrelated, encompassing low public literacy, weak nadzir capacity, insufficient fiscal incentives, and digitalization deficits; and (3) effective optimization requires an integrated ecosystem approach comprising governance strengthening, digital platform development, and cross-sectoral institutional synergy. The novelty of this study lies in its integration of legal, institutional, technological, and literacy dimensions within a single unified analytical framework grounded in maqashid syariah — an approach not yet comprehensively undertaken in prior literature. The principal contribution is the formulation of an operational maqashid syariah-based cash waqf governance model relevant to the Indonesian context, alongside systemic policy recommendations actionable by key stakeholders.